Integration of Legal Certainty and Restorative Justice in the Phases of General Criminal Investigation : An Examination of Law Enforcement by the Indonesian National Police - Johan Rofi; Fauzie Yusuf Hasibuan; Lilik Mulyadi (International Journal of Law and Society, 2025)
This research aims to elucidate the significance of restorative justice during the investigative phase and the legal assurance for investigators who apply restorative justice in cases of party noncompliance with the agreement. The author employs normative legal research, which involves the collection and analysis of legal documents pertinent to the subject at hand. This legal research employs the statute and case approaches. This writing employs primary and secondary legal materials. This article conducts prescriptive research. The findings of this research indicate that, initially, the concept of restorative justice during the investigative phase prioritizes substantive justice over procedural justice. We seek to establish substantive justice as the cornerstone of our rule of law, as it presents a promising opportunity for enhancing national well-being. The rule of law in Indonesia ought to foster the well-being of its citizens, and for this purpose, the notion of restorative justice, synonymous with substantive justice, is selected. Secondly, investigators lack legal clarity while implementing restorative justice if the participating parties violate the agreement. It may evolve into a complex issue when investigators seek to address broad criminal charges via restorative justice. The restorative justice concept is not acknowledged in general criminal offenses, although being governed by the Police Chief Regulation. Nonetheless, it is perceived that it still fails to offer legal certainty to investigators in the event of a future breach of contract or if the reported party defaults on their commitment or repeats their conduct.